Parallel and Distributed Processing: 10 IPPS/SPDP'98 Workshops Held in Conjunction with the 12th International Parallel Processing Symposium and 9th Symposium on Parallel and Distributed Processing Orlando, Florida, USA, March 30 – April 3, 1998 Proceedings - Rolim, José (Lecture Notes in Computer Science, 1998)
This book constitutes the refereed proceedings of 10 international workshops held in conjunction with the merged 1998 IPPS/SPDP symposia, held in Orlando, Florida, US in March/April 1998. The volume comprises 118 revised full papers presenting cutting-edge research or work in progress. In accordance with the workshops covered, the papers are organized in topical sections on reconfigurable architectures, run-time systems for parallel programming, biologically inspired solutions to parallel processing problems, randomized parallel computing, solving combinatorial optimization problems in parallel, PC based networks of workstations, fault-tolerant parallel and distributed systems, formal methods for parallel programming, embedded HPC systems and applications, and parallel and distributed real-time systems.